Interspecific hybridization in Pleurotus species - R.K. SHARMA, D. BAHUKHANDI and (Indian Phytopathology, 2012)
Interspecific hybridization studies were carried out between P/eurotus sajor-caju, P. sapidus and P. cornucopiae for obtaining better quality strains. The resultant hybrids were categorised on phenotypic basis into two categories. In first group, hybrids obtained were similar in appearance, yield and colour etc. with either of their parents. The second group hybrids had blending of characters of their parents and possessing the yield potential more or less similar to them. A specific hybrid (hybrid no. 3) obtained with mating between P. sajor-caju and P. cornucopiae, in which the shape and size of the sporophore was similar to P. sajor-caju and white colour was resembling with P. cornucopiae. The total average yield of this hybrid was found to be 23.3 per cent more than the parent.